The Impact of Biofloc on Fish Growth Indicators and Health Risks Assesment from Polyethylene Terephthalate Microplastic Contamination - Afriani, Dian Rizky; Deswati; Rahmiana Zein (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
This study aims to evaluate the effects of biofloc technology on the growth performance of Nile tilapia (Oreochromis niloticus) and to assess potential health risks associated with polyethylene terephthalate (PET) microplastic contamination in aquaculture systems. Three treatments were applied: aquaculture without biofloc and microplastics, aquaculture with biofloc but without microplastics, and aquaculture with biofloc combined with PET microplastics. The novelty of this research lies in the integration of biofloc technology with a quantitative health risk assessment approach aspect that has received limited attention in previous studies. Furthermore, this study specifically utilizes PET microplastics, which differ in physicochemical properties and toxicological potential from the commonly studied polyethylene (PE) microplastics. The results revealed that the best performance was observed in the treatment with biofloc but without microplastics, showing an average body weight (ABW) of 5.478 g/fish, an average daily gain (ADG) of 2.343 g/fish/day, and a specific growth rate (SGR) of 4.208%. In terms of health risk, this treatment also demonstrated low to moderate risk levels, with a Polymer Load Index (PLI) of 2.53, a Potential Health Index (PHI) of 11, and a Potential Ecological Risk Index (PERI) of 10. These findings indicate that biofloc technology is not only effective in enhancing fish growth performance but also contributes to mitigating the adverse impacts of microplastic contamination on fish health and food safety in aquaculture systems.